Prinsip-Prinsip Penegakan Hukum Dalam Perspektif Al-Qur’an - Abdul Majid, Zamakhsyari (Almarhalah | Jurnal Pendidikan Islam, 2017)
Al-Quran legal debate and strategy in an effort to improve justice for human life. The legal principles enforced in the life of the community can be seen in the implementation aspect. This writing examines and examines and the substance of law enforcement that is principally seen in the perspective of Qur'anic interpretation as well as the legal problems that are in the community environment. Writing uses the method of tafsir maudhu'I as one of the main points in the principle of law enforcement in the view of the Qur'an. The existence of the law universally becomes an integral part of humanity. It is an objective and an analysis of conditions that every human can feel without looking behind him.